Promoting informed decision making about maternal pertussis vaccination: the systematic development of an online tailored decision aid and a centering-based group antenatal care intervention - Anraad, Charlotte; van Empelen, Pepijn; Ruiter, Robert A. C.; Rijnders, Marlies; van Groessen, Katja; van Keulen, Hilde M. (Frontiers in Public Health, 2024)
Introduction Maintaining and enhancing vaccine confidence continues to be a challenge. Making an informed decision not only helps to avoid potential future regret but also reduces susceptibility to misinformation. There is an urgent need for interventions that facilitate informed decision-making about vaccines. This paper describes the systematic development of two interventions designed to promote informed decision making and indirectly, acceptance of maternal pertussis vaccination (MPV) in the Netherlands. Materials and Methods The 6-step Intervention Mapping (IM) protocol was used for the development of an online tailored decision aid and Centering Pregnancy-based Group Antenatal Care (CP) intervention. A needs assessment was done using empirical literature and conducting a survey and focus groups (1), intervention objectives were formulated at the behaviour and determinants levels (2), theoretical methods of behaviour change were selected and translated into practical applications (3), which were further developed into the two interventions using user-centred design (4). Finally, plans were developed for implementation (5) and evaluation (6) of the interventions. Results The needs assessment showed that pregnant women often based their decision about MPV on information sourced online and conversations with their partners, obstetric care providers, and peers. Responding to these findings, we systematically developed two interactive, theory-based interventions. We created an online tailored decision aid, subjecting it to four iterations of testing among pregnant women, including those with low literacy levels. Participants evaluated prototypes of the intervention positively on relevance and usability. In addition, a CP intervention was developed with midwives. Conclusion Using IM resulted in the creation of an online decision aid and CP intervention to promote informed decision making regarding MPV. This description of the systematic development of the interventions not only serves to illustrate design rationales, it will also aid the interpretation of the evaluation of the interventions, the development of future interventions promoting informed decision and acceptance of vaccines, and comparisons with other interventions.